Adipose tissue and metabolic syndrome: too much, too little or neither. (13th September 2015) - Grundy, Scott M.
Abstract Obesity is strongly associated with metabolic syndrome. Recent research suggests that excess adipose tissue plays an important role in development of the syndrome. On the other hand, persons with a deficiency of adipose tissue (e.g. lipodystrophy) also manifest the metabolic syndrome. In some animal models, expansion of adipose tissue pools mitigates adverse metabolic components (e.g. insulin resistance, hyperglycaemia and dyslipidemia). Hence, there are conflicting data as to whether adipose tissue worsens the metabolic syndrome or protects against it. This conflict may relate partly to locations of adipose tissue pools. For instance, lower body adipose tissue may be protective whereas upper body adipose tissue may promote the syndrome. One view holds that in either case, the accumulation of ectopic fat in muscle and liver is the driving factor underlying the syndrome. If so, there may be some link between adipose tissue fat and ectopic fat. But the mechanisms underlying this connection are not clear. A stronger association appears to exist between excessive caloric intake and ectopic fat accumulation. Adipose tissue may act as a buffer to reduce the impact of excess energy consumption by fat storage; but once a constant weight has been achieved, it is unclear whether adipose tissue influences levels of ectopic fat. Another mechanism whereby adipose tissue could worsen the metabolic syndrome is through release of adipokines. This is an intriguing mechanism, but the impact of adipokines on metabolic syndrome risk factors is uncertain. Thus, many potential connections between adipose tissue and metabolic syndrome remain to unravelled.